The Invincible Iron Man - Dougall, Alastair; Rousseau, Craig; Hi-Fi Colour Design (New York Marvel Press, 2012)
Iron Man fights Crimson Dynamo after the testing of a new spacecraft
comic stories
1
Keywords: Iron Man -- (Fictitious character) -- Juvenile fiction; Space ships -- Juvenile fiction; Superheroes -- Juvenile fiction